The public rituals of life, death, and resurrection in Tlayacapan, Morelos (Mexico) - Jackson, Robert H. (Cambridge Scholars Publishing, 2020)
A process of social, cultural, and religious change occurred in central Mexico starting in the sixteenth century, following the Spanish conquest. Missionaries from different religious orders attempted to convert the indigenous peoples of central Mexico to Catholicism, and a part of this process involved the imposition of a new ritual cycle on the existing Mesoamerican cycle that governed agriculture and the cosmic order. This study describes the evolution and modern practice of the public ritual of life, death, and resurrection in Tlayacapan, Morelos. Tlayacapan is a community located in north.